South-Eastern dialect’s features in the poetry collection of Ivan Manzhura “Stepp’s thoughts and songs” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
In the present article the  lexical, phraseological, phonetical, morphological and syntectical peculiarities of South-Eastern dialects fixed in the poetry of Ivan Manzhura at the end of the 19 th century are described.
Keywords: living folk language; dialect lexics; phonetical, morphological, synthectical traits; language and literary norms